A Phenomenological Study of Arabic Language Environment to Improve Students' Speaking Skills at Modern Islamic Boarding School - Eisya Nautika Rahmi; Mia Nurmala; Yayan Nurbayan; Syukran Syukran; Ananda Muhammad Faza (Mantiqu Tayr: Journal of Arabic Language, 2024)
The language environment has an important role in facilitating students in developing language skills. The fact found by researchers in the field that the Modern Islamic Boarding School Assalam Putri Sukabumi is one of the boarding schools that applies the language environment. The purpose of this study was to determine the Arabic language environment implemented at the Modern Islamic Boarding School Assalam Putri Sukabumi and to find out the students’ perceptions of the application of the Arabic language environment in improving maharah al-kalam. This research uses a qualitative approach, and the type of phenomenological research with data collection techniques used are interviews, observation and documentation. After the data is collected, data analysis techniques are carried out using thematic analysis techniques. The participants in this study were 5th grade students numbering 15 students. In addition, it also involved ustadzah and students of the language section management, and Arabic language teachers. The results obtained are the the Arabic language environment at the Modern Islamic Boarding School Assalam Putri Sukabumi is divided into formal and informal environments, also supported by language programs to improve students speaking skills. The students’ perception of the Arabic language environment in this boarding school shows a positive response. The implementation of the language environment in this boarding school is very influential for students speaking skills, because with the language environment, students become accustomed to using Arabic. This research is expected to enrich the insight of scientific development, especially in the world of research and Arabic language science. For further research, the researcher suggests analyzing the influence of the language environment on the 4 maharah lughawiyah and knowing the perceptions from the side of the teacher or even the head of the boarding school.